Implementation of digitalization of police record certificate or Surat Keterangan Catatan Kepolisian (SKCK) services at the Polresta Mamuju - H., Hardiansyah; Herman, Herman; Rahayu, Rahayu; Nur'Iva, Muhammad Irvan (Priviet Social Sciences Journal, 2026)
This study aims to analyze the implementation of digitization of SKCK services at the Polresta Mamuju. This study uses a qualitative method with a descriptive approach to provide a comprehensive overview of the implementation of digitization of SKCK services in the Polresta Mamuju. Data were collected through observation, interviews, and documentation to obtain in-depth and comprehensive information about the process of implementing the digitization of SKCK services at the Polresta Mamuju. The results of the study show that the implementation of digitization of SKCK services at the Polresta Mamuju has been quite effective and structured can be seen in the communication aspect, in its implementation, officers actively provide gradual explanations in simple language regarding the flow of online registration, verification, fingerprinting, and SKCK printing, as well as providing assistance for applicants who experience difficulties. In terms of resources, despite situational technical obstacles, the available resources are able to support the effectiveness of digitizing SKCK services and have a positive impact on time efficiency and service quality compared to manual systems. The aspect of the disposition, SKCK service officers, and the community, towards the implementation of digitization of SKCK services at the Polresta Mamuju shows a positive and supportive trend. The aspect of bureaucratic structure, in the implementation of digitization of SKCK services at the Polresta Mamuju has been prepared clearly, systematically, and runs in accordance with the applicable Standard Operating Procedures (SOP). Although there are still administrative obstacles such as data input errors, completeness of documents, and suggestions related to a more detailed notification system, overall the bureaucratic structure implemented has supported the orderliness, effectiveness, and improvement of the quality of digital-based SKCK services at the Polresta Mamuju.